An experimental study on flow induced motion and energy harvesting of cylinders with different cross sections - Song, Ronglai; Xu, Peng; Jiang, Changqing; Zhang, Yuan; Li, He (Frontiers in Marine Science, 2024)
Thank you for the valuable feedback provided by you and the reviewers. These comments have been instrumental in enhancing the quality of the manuscript. The manuscript has been carefully revised to clarify its logic and improve its overall quality. All changes have been highlighted in red and yellow within the revised manuscript. Responses to the reviewers ' comments have been provided point by point, with corresponding modifications clearly indicated. Full details of the revisions are included. We hope that the responses and modifications are satisfactory and that the manuscript is now suitable for publication.Reviewer #1: This article proposes an oscillator combining a rod attachment unit and a non-circular cross-section. Utilizing this oscillator, the Flow-induced motion energy conversion system (FIMECS) can effectively utilize ocean current energy. Simultaneously, oscillators of various shapes are compared, and experimental data are analyzed in this article. Additionally, Visual analysis is added to the result analysis in this article, expanding the range of low water current velocity measurements from 0.05 m/s to 0.75 m/s. The results demonstrate that compared with the traditional circular oscillator structure, the Circular-attachments Oscillator and Circular-T shaped-appendage Oscillator improve the energy harvesting performance. The integrated device has the potential to serve as a self-powered water current velocity sensor and a subsea micropower supply simultaneously, offering a versatile solution for energy harvesting from low-velocity ocean currents. Thus, this reviewer recommends this article be published in Frontiers In Marine Science. However, several questions need to be addressed before the final acceptance.